2017
DOI: 10.4018/ijdsst.2017040104
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making Support Systems in Quality Management of Higher Education Institutions

Abstract: The provision of high-quality educational services is a mandatory objective for Higher Education Institutions (HEIs) nowadays. Consequently, HEIs implement Quality Management System (QMS) process frameworks. A core managerial activity conducted in these QMS is decision making, which impacts the overall quality of the provided HEI's educational services. This managerial context found in HEIs demands an adequate and reliable managerial decision-making support. In this article, we elaborate a new Process-Task-Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
(90 reference statements)
1
9
0
Order By: Relevance
“…The findings concur with earlier research on using information generated from quality assurance for decision-making in that some key information is available but not necessarily used for decision-making (Martin, Parikh, 2017). In their selective review of the utilization of decisionmaking support systems for making decisions in HEPs, Mora et al (2017) found that these systems have been present. Still, their utilization for quality improvement is insufficient and partially deployed.…”
Section: Use Of Information To Assure Qualitysupporting
confidence: 84%
“…The findings concur with earlier research on using information generated from quality assurance for decision-making in that some key information is available but not necessarily used for decision-making (Martin, Parikh, 2017). In their selective review of the utilization of decisionmaking support systems for making decisions in HEPs, Mora et al (2017) found that these systems have been present. Still, their utilization for quality improvement is insufficient and partially deployed.…”
Section: Use Of Information To Assure Qualitysupporting
confidence: 84%
“…Furthermore, many authors have argued strongly for more holistic and integrated approaches to QM Dalrymple, 2002, 2005;D'Andrea and Gosling, 2005;Kleijnen et al, 2014), although empirical studies from a range of countries and institutions have suggested that many QM systems, at least in earlier years, tended to be characterised by having a more managerial and an employment-oriented focus (Harvey, 1995(Harvey, , 1998Barrow, 1999;Ottewill and Macfarlane, 2004;Brunetto and Farr-Wharton, 2005;Popli, 2005;Rosa et al, 2006;Law, 2010;Talib et al, 2011;Soria-García and Martínez-Lorente, 2014;Teeroovengadum et al, 2016). However, in more recent overviews of the QM literature, Manatos et al (2017) and Mora et al (2017) have argued that QM systems seem to move towards becoming more integrated in the general governance of higher education institutions, and that there is a trend towards more comprehensive QM systemsat least according to what is reported in international journals (see also Sarrico, 2010). Still, as Manatos et al (2017) note, a problem with much of the current literature is that it is often quite theoretical, focussing more on the normative designthat is, formal ambitions and objectivesthan on the actual functioning of existing QM systems in practice, and the involvement of different actors in these practices.…”
Section: Introductionmentioning
confidence: 99%
“…Decision making can be defined as a management process for framing a given situation in which a decision needs to be made. By defining a decision model, made up of a set of actions and evaluation criteria, it is possible to select the most appropriate course of action and even learn from the decision-making process [13].…”
Section: Decision Making In Heismentioning
confidence: 99%